2020
DOI: 10.3847/1538-4357/ab8631
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Field Variance on the Hα Luminosity Function with the New Numerical Galaxy Catalog (ν2GC)

Abstract: We construct a model of Hα emitters (HAEs) based on a semi-analytic galaxy formation model, the New Numerical Galaxy Catalog (ν 2 GC). In this paper, we report our estimate for the field variance of the HAE distribution. By calculating the Hα luminosity from the star-formation rate of galaxies, our model well reproduces the observed Hα luminosity function (LF) at z = 0.4. The large volume of the ν 2 GC makes it possible to examine the spatial distribution of HAEs over a region of (411.8 Mpc) 3 in the comoving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…For the observed Hα LFs (figure 10), the faint end slope is flatter than the PDR1 result as well as the results from the other previous studies, which makes the observed LF more consistent with the LF expected from a semi-analytic model (Ogura et al 2020). For the observed [OIII] LFs (figure 11), the number density is larger than that of the PDR1 LF.…”
Section: Emission-line Luminosity Functionssupporting
confidence: 74%
See 1 more Smart Citation
“…For the observed Hα LFs (figure 10), the faint end slope is flatter than the PDR1 result as well as the results from the other previous studies, which makes the observed LF more consistent with the LF expected from a semi-analytic model (Ogura et al 2020). For the observed [OIII] LFs (figure 11), the number density is larger than that of the PDR1 LF.…”
Section: Emission-line Luminosity Functionssupporting
confidence: 74%
“…The ∼ 10 deg 2 NB imaging surveys by Sobral et al (2015) and Stroe & Sobral (2015) show that a large survey volume of >3.5-5.0×10 5 Mpc 3 can overcome cosmic variance and then the luminosity functions of emission-line galaxies are derived with an error of < 10%. From a theoretical point of view, Ogura et al (2020) investigate the influence of the field variance in Hα emission-line galaxies at z = 0.4 using a semi-analytic model for the galaxy formation, the New Numerical Galaxy Catalog (ν 2 GC), and find that a survey area of more than 15 deg 2 is required to restrict the uncertainties in the luminosity functions of Hα emitters at z = 0.4 to less than ∼ 10%.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have theoretically evaluated the cosmic variance of galaxies at high redshift (e.g. Somerville et al 2004;Trenti & Stiavelli 2008;Ogura et al 2020;Bhowmick et al 2020;Ucci et al 2021). Ogura et al (2020) used a semi-analytic model of galaxy and AGN formation, the New Numerical Galaxy Catalog (ν 2 GC; Makiya et al 2016;Shirakata et al 2019), to evaluate the cosmic variance of Hα emitters at z = 0.4.…”
Section: Introductionmentioning
confidence: 99%
“…Somerville et al 2004;Trenti & Stiavelli 2008;Ogura et al 2020;Bhowmick et al 2020;Ucci et al 2021). Ogura et al (2020) used a semi-analytic model of galaxy and AGN formation, the New Numerical Galaxy Catalog (ν 2 GC; Makiya et al 2016;Shirakata et al 2019), to evaluate the cosmic variance of Hα emitters at z = 0.4. They also quantified how cosmic variance depends on survey volume.…”
Section: Introductionmentioning
confidence: 99%